Co-Utilization of Clinical Ethics and Palliative Care Consultations in Hospitalized Patients - Benjamin M. Nikitin; Krishna Chokshi; Jolion McGreevy; Joel Rowe; Ayla R. Pelleg; Laura P. Gelfman (American Journal of Hospice and Palliative Medicine®, 2026)
Context Clinical ethics and palliative care are distinct consultation services that are increasingly used in hospitals to support complex medical decisions, particularly at the end of life. Concurrent utilization of these services is poorly characterized despite documented benefits of collaboration. Objectives To compare demographic, clinical, and utilization patterns among patients who received an inpatient clinical ethics consultation and did or did not receive a palliative care consultation. Methods We conducted an exploratory retrospective cohort study as part of a broader quality improvement initiative in a large, urban academic health system of all adult inpatient encounters with ethics consultations from 1/1/2024 – 5/31/2025. We collected electronic health record data including demographic, clinical, utilization data, and receipt of palliative care. We compared patients who did and did not receive palliative care using descriptive and bivariate analyses. Results Of 264 encounters with a clinical ethics consultation, 113 (42.8%) had a palliative care consultation, and palliative care consultations preceded ethics consultations in most cases (80.5%). There were no statistically significant differences in demographic and clinical characteristics between the two groups; patients who received both ethics and palliative care consultations had more intensive care unit days, higher predicted mortality, and higher in-hospital mortality. Conclusion Clinical ethics consultations commonly co-occur with palliative care, especially among clinically complex patients. The observed variability in consultation timing and sequencing supports further evaluation of structured collaboration frameworks between the two services to potentially improve utilization of these limited resources and better align care with patient goals.